A Note on the Physical and Mechanical Properties of Prunus nepaulensis (Arupati) - Sekhar, A. C.; Gulati, A. S. (Indian Forester, 1972)
Mechanical tests were done in green, air-dry and kiln-dry conditions on small clear specimens obtained from 10 logs from 10 different naturally grown trees of Prunus nepaulensis received from Kalimpong Division, W. Bengal. The results have been compared with Teak. Calculated values based on strength specific gravity formulae have also been given for comparison.